PELAKSANAAN JAMINAN PEMELIHARAAN (MAINTENANCE BOND) SEBAGAI JAMINAN PEKERJAAN KONTRUKSI ANTARA PT. ASURANSI MEGA PRATAMA CABANG PADANG DENGAN CV. MERPATI - Febbyana, Febbyana; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Surety Bond is a form of written agreement between three parties, where the surety (surety), provides guarantees to the second party (principal) for the benefit of third parties (obligee). One type of surety bond is maintenance bond. Maintenance bond is a guarantee against damage to work or material that occurs after the job is completed.This type of research can be classified in the study of sociological law, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in Padang while the population and sample are all parties related to the problems examined in this study, data sources used, primary data, secondary data, and tertiary data, data collection techniques in this study by interview and literature study.The conclusions that can be obtained from the results of the study are: First, the legal relationship between CV. Merpati with PT. Asuransi Mega Pratama, where the maintenance guarantee agreement has fulfilled the legal requirements of the agreement as stipulated in Article 1320 of the Civil Code. The legal relationship arising from the maintenance guarantee agreement is a mutual legal relationship that can give rise to the rights and obligations of each party. Implementation of the responsibilities of CV. Merpati against PT. Asuransi Mega Pratama has not yet been fulfilled, one of which is the payment of compensation for the compensation experienced by the Tanah Datar District Public Works Office.Keywords: Guarantee, Maintenance, Work , Contruction.